PENGGUNAAN MEDIA AUDIO VISUAL DALAM PENGAJARAN MENULIS PERMULAAN - Tegi, Lidia Krisdayanti; Ali, Muhamad; Linarsih, Andini (Universitas Tanjungpura, 2023)
This study aims to describe the use of audio-visual media to improve early childhood writing skills. The method used is descriptive qualitative. The subject of the study was a teacher of group B. The data collection techniques used in this study were interviews, observations, and documentation. Data analysis is carried out, namely data collection, data reduction, data presentation, and drawing conclusions. The data validity technique is Triangulation. The results of this study show that: 1 has been planned to learn the ability to write using audio-visual media in children 5-6 years. 2. Learning has beencarried out using audio-visual media. 3. The use of audio-visual media can improve the writing skills of children aged 5-6 years. The conclusion in this study is that the audio-visual method was deliberately tread by the teacher to improve early writing ability of children aged 5-6 years.